JMJD-5/KDM8 regulates H3K36me2 and is required for late steps of homologous recombination and genome integrity - Amendola, Pier Giorgio; Zaghet, Nico; Ramalho, João J.; Vilstrup Johansen, Jens; Boxem, Mike; Salcini, Anna Elisabetta (PLoS genetics, 2017)
The eukaryotic genome is organized in a three-dimensional structure called chromatin, constituted by DNA and associated proteins, the majority of which are histones. Post-translational modifications of histone proteins greatly influence chromatin structure and regulate many DNA-based biological processes. Methylation of lysine 36 of histone 3 (H3K36) is a post-translational modification functionally relevant during early steps of DNA damage repair. Here, we show that the JMJD-5 regulates H3K36 di-methylation and it is required at late stages of double strand break repair mediated by homologous recombination. Loss of jmjd-5 results in hypersensitivity to ionizing radiation and in meiotic defects, and it is associated with aberrant retention of RAD-51 at sites of double strand breaks. Analyses of jmjd-5 genetic interactions with genes required for resolving recombination intermediates (rtel-1) or promoting the resolution of RAD-51 double stranded DNA filaments (rfs-1 and helq-1) suggest that jmjd-5 prevents the formation of stalled postsynaptic recombination intermediates and favors RAD-51 removal. As these phenotypes are all recapitulated by a catalytically inactive jmjd-5 mutant, we propose a novel role for H3K36me2 regulation during late steps of homologous recombination critical to preserve genome integrity.